2021
DOI: 10.1108/bij-10-2020-0546
|View full text |Cite
|
Sign up to set email alerts
|

SWOT analysis of Industry 4.0 variables using AHP methodology and structural equation modelling

Abstract: PurposeAdvanced digitalization techniques combined with artificial intelligence and automated robotic systems have created “Smart” organizations resulting in a new revolution in the industrial production systems as Industry 4.0 (I4.0). The research is aimed to do a meticulous scanning of internal and external environment pertaining to I4.0 implementation in the manufacturing industry in India.Design/methodology/approachA survey was conducted among the manufacturing managers and information technology professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Key ingredients for assessing Industry 4.0 readiness for organizations have been identified by the authors Sony and Naik (2020). In their research, Jain et al (2022) carried out a detailed scan of the internal and external environment related to the implementation of I4.0, and the results showed that increased productivity and efficiency are the greatest strength of I4.0, while the greatest weakness is the need for specialized training and skills. The biggest opportunity is the increase of customers' trust in internet transactions, and the biggest threat is the resistance of employees toward the adoption of new technologies.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Key ingredients for assessing Industry 4.0 readiness for organizations have been identified by the authors Sony and Naik (2020). In their research, Jain et al (2022) carried out a detailed scan of the internal and external environment related to the implementation of I4.0, and the results showed that increased productivity and efficiency are the greatest strength of I4.0, while the greatest weakness is the need for specialized training and skills. The biggest opportunity is the increase of customers' trust in internet transactions, and the biggest threat is the resistance of employees toward the adoption of new technologies.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Considering specifically the human factor, the biggest threat to the implementation of Industry 4.0 is related to the resistance of workers to adopt new technologies and the need for training presents itself as the biggest weakness (Jain et al, 2021). Thus, training and continuous professional development deserve special attention and importance for Industry 4.0 (Kaya et al, 2020;Schallock et al, 2018).…”
Section: Theoretical Background Industry 40 and Trainingmentioning
confidence: 99%
“…SWOT-AHP analysis has been successfully applied in a number of recent studies (Jain et al, 2021;Stefan et al, 2021;Veličkovska, 2022;Shiwakoti & Regmi, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%